Hip thrust and back squat training elicit similar gluteus muscle hypertrophy and transfer similarly to the deadlift - Plotkin, Daniel L.; Rodas, Merlina A.; Vigotsky, Andrew D.; McIntosh, Mason C.; Breeze, Emma; Ubrik, Rachel; Robitzsch, Cole; Agyin-Birikorang, Anthony; Mattingly, Madison L.; Michel, J. Max; Kontos, Nicholas J.; Lennon, Sarah; et al. (Frontiers in Physiology, 2023)
We examined how set-volume equated resistance training using either the back squat (SQ) or hip thrust (HT) affected hypertrophy and various strength outcomes. Untrained college-aged participants were randomized into HT (n=18) or SQ (n=16) groups. Surface electromyograms (sEMG) from the right gluteus maximus and medius muscles were obtained during the first training session. Participants completed nine weeks of supervised training (15-17 sessions), before and after which gluteus and leg muscle cross-sectional area (mCSA) was assessed via magnetic resonance imaging. Strength was also assessed prior to and after the training intervention via threerepetition maximum (3RM) testing and an isometric wall push test. Gluteus mCSA increases were similar across both groups. Specifically, estimates [(−) favors HT; (+) favors SQ] modestly favored the HT versus SQ for lower [effect ± SE, −1.6 ± 2.1 cm 2 ; CI95% (−6.1, 2.0)], mid [−0.5 ± 1.7 cm 2 ; CI95% (−4.0, 2.6)], and upper [−0.5 ± 2.6 cm 2 ; CI95% (−5.8, 4.1)] gluteal mCSAs but with appreciable variance. Gluteus medius+minimus [−1.8 ± 1.5 cm 2 ; CI95% (−4.6, 1.4)] and hamstrings [0.1 ± 0.6 cm 2 ; CI95% (−0.9, 1.4)] mCSA demonstrated little to no growth with small differences between groups. mCSA changes were greater in SQ for the quadriceps [3.6 ± 1.5 cm 2 ; CI95% (0.7, 6.4)] and adductors [2.5 ± 0.7 cm 2 ; CI95% (1.2, 3.9)]. Squat 3RM increases favored SQ [14 ± 2 kg; CI95% (9, 18),] and hip thrust 3RM favored HT [−26 ± 5 kg; CI95% (−34, −16)]. 3RM deadlift [0 ± 2 kg; CI95% (−4, 3)] and wall push strength [−7 ± 12 N; CI95% (−32, 17)] similarly improved. All measured gluteal sites showed greater mean sEMG amplitudes during the first bout hip thrust versus squat set, but this did not consistently predict gluteal hypertrophy outcomes. Squat and hip thrust training elicited similar gluteal hypertrophy, greater thigh hypertrophy in SQ, strength increases that favored exercise allocation, and similar deadlift and wall push strength increases.